Validated Stability Indicating and Assay Method Development of Linagliptin in Formulation by RP-HPLC Using Quality by Design - Ganorkar, Anvesha V.; Askarkar, Sonali S.; Gupta, Krishna R.; Umekar, Milind J. (Orbital: The Electronic Journal of Chemistry, 2020)
Quality by Design (QbD) approach was used to facilitate stability indicating HPLC method development of linagliptin (LIN) in tablet dosage form. The method was developed using the PrimesilC18, 250 mm x 4.6 mm, 5µ column using the mobile phase consisting of 0.3% TEA: methanol. (60:40 v/v) pH 4.5 adjusted with o-phosphoric acid. Design of experiment tools was used for optimization of the chromatographic conditions. A three-level Box-Behnken design was employed and statistical analysis of the experimental data showed the significant influential factor of chromatographic conditions. The design space suggested that the current center point parameters could be further modified results with better acceptability for the response parameters. The performance of the optimized method was validated according to ICH guidelines.  Linagliptin was exposed to different stress conditions (acid, base, neutral, oxidative, thermal and photolytic) and chromatograms recorded at 292 nm. The degradation of linagliptin followed zero order kinetics for acidic, oxidative and neutral hydrolysis whereas for basic hydrolysis first-order kinetics under experimental conditions. Peak purity plots were evaluated for the degraded sample. The results obtained suggest that the method can be adopted for its analysis and is stability indicating as well. The three-level design helps in understanding the interaction among factors rather than one time one variation as carried out in routine method development.DOI: http://dx.doi.org/10.17807/orbital.v12i2.1194